Research on the Method of Collecting Genre Seals from the Perspective of National Cultural Inheritance: A Case Study of Late Qing Dynasty Literati Seal Carving with Ancient Brick Inscriptions - Xu, Shiyi (Journal of Social Science and Humanities, 2025)
The art of seal carving in the late Qing Dynasty developed to a very prosperous point, and achieved extremely high artistic achievements. The phenomenon of the literati seal carving art is the act of the seal carver on the basis of the existing art, and then absorbing and creating other artistic elements and borrowing similar artistic elements. This paper takes the characters in the late Qing Dynasty as a clue to study the objects and methods of the literati seal carvers in the late Qing Dynasty from the perspective of the study of gold and stone, and at the same time reveals the development and evolution of the seal carving art in the late Qing Dynasty and points out its outstanding achievements, the seal carving art is placed in the context of the social and cultural life of the late Qing Dynasty, and comprehensively discusses the objects and sources of the seal carvers in this period. This is of great significance for people to better understand and inherit the seal carving art of the late Qing Dynasty. In the context of the gradual development of epigraphy, this paper takes the more representative inscriptions of epigraphy as an example, explores the source of the literati’s seal carving method from the characters in the unearthed ancient brick inscriptions, and studies the inscriptions they took into print. Through the study of the scope of seal carving art, this paper summarizes and discusses the development of the literati seal carvers in the development of seal carving in later generations and the promotion of the aesthetics and innovation of seal carving art.